Strategi Membangun Brand Awareness Melalui Islamic Branding di Pondok Pesantren Nurul Jadid Wilayah Al-Mawaddah - Muhammad Ainul Yaqin; Nurul fadilah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
. Efforts to develop Islamic educational institutions are a necessity in the context of educational progress, especially in Islamic boarding schools. Reform of Islamic educational institutions can be enhanced through improving the quality of education, which is also a need and hope of society that must be responded to positively by educational institutions. Quality education involves institutional efforts to provide satisfactory services for students. The high level of public interest and support for educational institutions needs to be considered and implemented by managers. Therefore, institutional managers are expected to continue to improve their abilities in facing competition. In this case, the brand image reflects the image of the educational institution, and a positive image will provide a good assessment from the public. With this positive view, people will naturally believe that the institution has superior quality. A plan to increase brand awareness with the aim of increasing the competitiveness of educational institutions involving continued development of educational products that have been proven successful. In addition, adding superior products that are difficult for competitors to imitate can provide a stronger competitive advantage, supporting increased competitiveness of educational institutions.